Editorial Board and Guideline for the Authors of the SOSIOHUMANIKA Journal, issue of May 2015 - SOSIOHUMANIKA, Editor Journal (ASPENSI in Bandung, Indonesia, 2015)
SOSIOHUMANIKA will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment, and analysis on the key issues surrounding the humanities and social sciences education and its various aspects. Analysis will be practical and rigorous in nature.Bandung, Indonesia: May 30, 2015.Prof. Dr. Abdul Rasyid AsbaVice Chief Editor of the SOSIOHUMANIKA Journal in Bandung, West Java, Indonesia.Â